2020
DOI: 10.1097/hjh.0000000000002535
|View full text |Cite
|
Sign up to set email alerts
|

Intervention study of the effect of insulation retrofitting on home blood pressure in winter: a nationwide Smart Wellness Housing survey

Abstract: Objective: The WHO's Housing and health guidelines (2018) listed ‘low indoor temperatures and insulation’ as one of five priority areas, and indicated insulation retrofitting to help mitigate the effect of low indoor temperatures on health. However, there is still not enough evidence for the effect of insulation retrofitting based on an objective index. Methods: We conducted a nonrandomized controlled trial comparing home blood pressure (HBP) between in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Except for one office study [ 43 ], eight studies were performed in residential buildings ( Table A10 ). Some studies reported that energy efficiency intervention in homes can improve asthma [ 77 , 78 ], respiratory symptoms [ 77 , 78 , 79 , 81 ], sinusitis [ 80 ], general health [ 80 , 83 ], satisfaction [ 80 , 81 ], and reduce blood pressure [ 84 ]. Furthermore, an improved mechanical ventilation rate in office buildings can improve SBS symptoms, productivity, and perceived indoor air quality [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for one office study [ 43 ], eight studies were performed in residential buildings ( Table A10 ). Some studies reported that energy efficiency intervention in homes can improve asthma [ 77 , 78 ], respiratory symptoms [ 77 , 78 , 79 , 81 ], sinusitis [ 80 ], general health [ 80 , 83 ], satisfaction [ 80 , 81 ], and reduce blood pressure [ 84 ]. Furthermore, an improved mechanical ventilation rate in office buildings can improve SBS symptoms, productivity, and perceived indoor air quality [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“… Francisco et al [ 83 ] 2017 United States Weatherization services Intervention Residential buildings General health 72 households 178 children and adults Energy efficiency retrofits can improve self-reported health. Umishio et al [ 84 ] 2020 Japan installation of outer walls, floor and/or roof insulation and replacement of windows Intervention Residential buildings Blood pressure 1009 households 1685 adults Energy efficiency insulation retrofitting in homes can reduce home blood pressure and reduce morning home systolic blood pressure of hypertensive patients. …”
Section: Table A1mentioning
confidence: 99%
“…A randomized controlled trial [ 32 ] indicated that instruction in home heating reduced morning SBP by 4.4 mmHg. Furthermore, an intervention study [ 33 ] revealed that insulation retrofitting of houses significantly reduced morning home SBP by 3.1 mmHg. Based on these results, heating use and highly insulated houses are both important for reducing BP levels.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal insulation and airtightness of houses affect the health of residents. [1][2][3][4][5][6][19][20][21][22] In New Zealand, a large-scale study of 4407 low-income residents (1350 households) revealed that residents living in houses with better insulation had higher self-assessments of their health status, fewer absences from school and work, and fewer hospitalizations for respiratory diseases. 1,2 Regarding airtightness, apartment buildings are more airtight than detached houses, resulting in increased condensation, mold, and dampness.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a room in an apartment is surrounded by other dwelling units; therefore, the outer surface area is small, resulting in better heat insulation and airtightness compared with detached houses. The thermal insulation and airtightness of houses affect the health of residents 1‐6,19‐22 . In New Zealand, a large‐scale study of 4407 low‐income residents (1350 households) revealed that residents living in houses with better insulation had higher self‐assessments of their health status, fewer absences from school and work, and fewer hospitalizations for respiratory diseases 1,2 .…”
Section: Introductionmentioning
confidence: 99%